Five-year outcomes after PCI or CABG for left main coronary disease - Stone, GW; Kappetein, AP; Sabik, JF; Banning, A (Massachusetts Medical Society, 2019)
BACKGROUND Long-term outcomes after percutaneous coronary intervention (PCI) with contemporary drug-eluting stents, as compared with coronary-artery bypass grafting (CABG), in patients with left main coronary artery disease are not clearly established.